An audit cycle of consent form completion: A useful tool to improve junior doctor training - Catherine Leng; Kavita Sharma (Indian Journal of Plastic Surgery)
Background: Consent for surgical procedures is an essential part of the patient's pathway. Junior doctors are often expected to do this, especially in the emergency setting. As a result, the aim of our audit was to assess our practice in consenting and institute changes within our department to maintain best medical practice. Methods: An audit of consent form completion was conducted in March 2013. Standards were taken from Good Surgical Practice (2008) and General Medical Council guidelines. Inclusion of consent teaching at a formal consultant delivered orientation programme was then instituted. A re-audit was completed to reassess compliance. Results: Thirty-seven consent forms were analysed. The re-audit demonstrated an improvement in documentation of benefits (91–100%) and additional procedures (0–7.5%). Additional areas for improvement such as offering a copy of the consent form to the patient and confirmation of consent if a delay occurred between consenting and the procedure were identified. Conclusion: The re-audit demonstrated an improvement in the consent process. It also identified new areas of emphasis that were addressed in formal teaching sessions. The audit cycle can be a useful tool in monitoring, assessing and improving clinical practice to ensure the provision of best patient care.